Narrative analysis and framing of Governor Brownback’s state funding crisis in 2015: a case study of press secretary Eileen Hawley - Hadfield, Molly Jaqueline (Kansas State University, 2019)
Sam Brownback’s tumultuous tenure as Governor of Kansas required talented public relations people to work with the media and help him sell his budget ideas to the state. His second of three Communications Directors, Eileen Hawley, served at the time of Brownback’s 2015 tax cuts that caused a massive budget shortfall, plunging the state into a financial crisis. This case study examines the effectiveness of framing strategies used by Hawley, who employed a more politically neutral stance during her messaging surrounding the Kansas budget shortfall. This study uses in-depth interviews with Hawley and Statehouse reporters to assess Hawley’s strategies in handling the ensuing financial crisis. Previous studies have shown that communications directors who present material in a more neutral manner gain the trust of the media, and therefore their frames have more saliency in the press. This study reveals mixed results in using such a strategy, with generally negative assessments from Capital reporters.
Keywords: Narrative analysis; Case study; Public information; Framing; Communications